Autobiographical memory and episodic future thinking in anorexia nervosa: a three-year follow-up - Johanna Louise Keeler; Valentina Cardi; Georgia Peters-Gill; Hubertus Himmerich; Kate Tchanturia; Janet Treasure (Journal of Eating Disorders)
Abstract Background People with anorexia nervosa (AN) show deficiencies with recalling specific details of autobiographical memories (AM). This may interfere with wider processes of self-narrative construction and identity building, which are a fundamental part of the recovery process. However, no studies have examined the temporal stability of AM deficiencies over time or their prognostic value in this population. Methods This study followed up adults with mostly longstanding AN that participated in a previous study examining AM and episodic future thinking (EFT) abilities after 3 years. A total of 20 participants with AN responded (44% of the original sample) and repeated a remotely administered written version of the Autobiographical Memory Test (AMT) and Episodic Future Thinking Task (EFT-T) and a series of questionnaires. The word lists used were identical to the previous study, but were alternated for the present study (i.e., participants viewing list A for the AMT previously saw list B in the follow-up). Task outcomes included AM and EFT specificity, vividness, difficulty to remember/imagine, positivity, realisticness and detailedness. Results Respondents had persistently high eating disorder psychopathology and comorbid psychiatric symptoms at follow-up. Body mass index (BMI) increased in most participants (n = 15), albeit the group average was 17.2 kg/m2. There was comparable performance on the AMT and EFT-T at both baseline and at follow-up. Analyses interrogating prognosis were not possible due to the homogeneity in ED-related outcomes, although baseline AM specificity was not related to BMI, ED symptoms, depressive symptoms or measures of identity functioning (i.e., consolidated identity, disturbed identity, or lack of identity), at follow-up. Conclusions Problems with retrieving specific details of AMs show temporal stability over time in people with longstanding AN. The prognostic value of AM specificity on ED outcomes remains unknown, which future well-controlled prospective longitudinal studies could address.